PENGARUH PROFESIONALISME, KOMITMEN PROFESIONAL DAN PENGALAMAN KERJA PADA PERTIMBANGAN TINGKAT MATERIALITAS AUDIT ATAS LAPORAN KEUANGAN - Meke Frank, Oki; Ariyanto, Dodik (E-Jurnal Akuntansi; Vol 17 No 3 (2016), 2016)
Differrences in individual perception of an auditor tend to be able to give consideration to the different users of financial statements and reflected in the difference in the decision-making of each auditor. The aims of this study is to determine the effect of professionalism, commitment professional, and work experience variable. KAP study was conducted in the province of Bali listed in the Directory of Certified 2016. The sampling method used non-probability sampling method with saturated sampling technique. On the other hand, data analysis technique used multiple linear regression analysis. Respondents of this study is 70 respondents, but only 47 respondents can prosessed. The result shown that the variable consideration of materiality levels can be explained by professionalism, commitment professional, and work experience.  Testing the hypothesis with t statistical test showed the variables of professionalism, commitment professional and work experience affect consideration of the level of audit materiality and statistically significant.
Keywords: Professionalism, Commitment Professional, Work Experience, Consideration of Materiality level